14. PEOPLE'S SATISFACTION WITH THE VOLUNTEER MEDICAL EXAMINATION PROGRAM OF THE FACULTY OF MEDICINE, DAI NAM UNIVERSITY IN PO LY NGAI COMMUNE, HOANG SU PHI DISTRICT, HA GIANG PROVINCE IN 2024 (Vietnam Journal of Community Medicine, 2024)
Objective: Describe people's satisfaction with the voluntary medical examination program of the Faculty of Medicine, Dai Nam University in Po Ly Ngai commune, Hoang Su Phi district, Ha Giang province in 2024.Subject and method: A cross-sectional descriptive study included 238 eligible and consenting residents in the voluntary medical examination program of the Faculty of Medicine, Dai Nam University in 2024.Results: This study showed that people were very satisfied with the voluntary medical examination program (overall assessment: 4.85 ± 0.35 points) (satisfaction rate > 96%). In particular, people were most satisfied with the paraclinical implementation stage (4.85 ± 0.36 points) and least satisfied with the program communication approach stage (4.71 ± 0.45 points). The satisfaction rate in the reception stage, paraclinical implementation stage, facilities, and overall assessment of the voluntary medical examination program reached 100%, and the satisfaction rate of people in the program communication approach stage was the lowest at 96.63%.Conclusion: The overall satisfaction level of people coming to the free medical examination in Po Ly Ngai commune, Hoang Su Phi district, Ha Giang province is 4.85/5 points, in which the satisfaction rate of people in general assessment in all stages of the program reached 100%. In particular, people are most satisfied with the physical facilities (4.87 ± 0.45 points) and least satisfied with the program communication access (4.71 ± 0.45 points).
Keywords: People's satisfaction; voluntary medical examination; Faculty of Medicine; Dai Nam University